PERAN SERTA MASYARAKAT DALAM MENGHADAPI KEMAJUAN TEKNOLOGI INFORMASI (ERA DIGITALISASI) - Habel Saud; Mikhael Udam; Yansen Alberth Reba; Felix Reba; Ahmad Sofyan (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2023)
The current community service seminar aimed to increase public insight regarding the use of information technology as a medium that expedites and facilitates educational, health, economic, business, socio-cultural and political activities. This activity for community service used lecture, discussion or question and answer methods. Then, the method for the problem-solving framework consisted of: 1) the preparation stage, 2) the discussion stage for community service material, and 3) the evaluation stage, as well as seminars related to community participation in dealing with advances in information in the digitalization era. This seminar activity involved elements of the local government which included the Kemtuk Gresi District/Sub-District Head, village heads in the Kemtuk Gresi District, the Kemtuk Gresi Customary Council and youth elements (KNPI of Kemtuk Gresi District) of Jayapura Regency, especially the millennial generation, community elements such as religious leaders , educational leaders, and traditional leaders. Based on the research results, 34 community members (97.14%) stated that science and technology (S&T) is beneficial in the globalization era for people's lives, but 1 community member stated that science and technology (S&T) does not necessarily bring benefits to life. Thus, it was concluded that most members of the community who attended the community service seminar on community participation in dealing with advances in information technology (digitalization era) understand and comprehend the positive and negative influences of science and technology for life and young people in the era of globalization. Meanwhile, a small number of people make use of science and technology in their daily lives both to support student learning activities, social activities and facilitate economics and business.